2016
DOI: 10.1161/circulationaha.115.012427
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Receptor Agonist Fingolimod Increases Myocardial Salvage and Decreases Adverse Postinfarction Left Ventricular Remodeling in a Porcine Model of Ischemia/Reperfusion

Abstract: Sphingosine-1-phosphate receptor activation with fingolimod during acute MI reduced infarct size via the reperfusion injury salvage kinase and survivor activating factor enhancement pathways, improved systolic LV function, and mitigated post-MI LV remodeling. Our data strongly support a cardioprotective role for sphingosine-1-phosphate receptor activation during MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
130
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(140 citation statements)
references
References 57 publications
8
130
0
2
Order By: Relevance
“…Neuropeptide Y is positively correlated in humans with LV wall thickness, LV mass index, and associated with a higher risk of concentric hypertrophy 35, 36. A new study by Santos‐Gallego et al showed that the involvement of Akt and ERK signaling is integral to cardiac remodeling in the remote myocardium of infarcted swine 37. Our findings indicate pressure‐overload‐induced hypertrophy is not associated with changes to Akt or ERK activation and are similar to recent work demonstrating chronic NPY infusion induces diastolic dysfunction and concurrent pathological cardiac hypertrophy, including increased fibrosis, independent of activated Akt/ERK signaling 38.…”
Section: Discussionsupporting
confidence: 89%
“…Neuropeptide Y is positively correlated in humans with LV wall thickness, LV mass index, and associated with a higher risk of concentric hypertrophy 35, 36. A new study by Santos‐Gallego et al showed that the involvement of Akt and ERK signaling is integral to cardiac remodeling in the remote myocardium of infarcted swine 37. Our findings indicate pressure‐overload‐induced hypertrophy is not associated with changes to Akt or ERK activation and are similar to recent work demonstrating chronic NPY infusion induces diastolic dysfunction and concurrent pathological cardiac hypertrophy, including increased fibrosis, independent of activated Akt/ERK signaling 38.…”
Section: Discussionsupporting
confidence: 89%
“…Activation of the RISK and SAFE pathways has been reported to decrease cardiomyocyte apoptosis and reduce myocardial oxidative stress [28]. Consistently, the antiapoptotic, anti-inflammatory and antioxidative effects of CO-HBOC pretreatment were accompanied by an activation of the RISK and SAFE pathways in our model.…”
Section: Discussionsupporting
confidence: 88%
“…Regulation of the RISK (reperfusion injury salvage kinase) pathway, involving Akt/ERK/GSK-3, and the SAFE (survivor activating factor enhancement) pathway, involving JAK/STAT3, are related to cardioprotection [28]. As shown in figure 9, exposure to hypobaric hypoxia did not change the activity of these pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Cardiomyocyte apoptosis is another leading cause of HF. 30 A TUNEL assay (Hoffman-La Roche Ltd) was performed to detect the apoptotic cardiac cells in the peri-infarct region 4 weeks after the injection. As shown in Figure 7, the NP-liraglutide group showed a significant reduction in the number of apoptotic cells (3.0%±0.3%) compared to the saline, NP and liraglutide groups (5.9%±0.7%, 5.1%±0.8% and 5.4%±0.8%, respectively, P,0.05).…”
mentioning
confidence: 99%